2020
DOI: 10.21203/rs.3.rs-19608/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MiR-125b promotes migration and invasion by targeting vitamin D receptor in renal cell carcinoma

Abstract: Background To investigate the expression of miR-125b and vitamin D receptor (VDR) in renal cell carcinoma (RCC) and assess the possible association between them. Then, to elucidate whether miR-125b can regulate the expression of VDR and affect proliferation and metastasis in RCC.Methods The expression of miR-125b was detected by quantitative real-time polymerase chain reaction (RT-PCR) in RCC cell lines. MiR-125b mimic and inhibitor were employed to measure the function and behavior of miR-125b in RCC cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Çaykara et al (27) indicated that abnormally downregulated miR-124 was associated with the tumor stage, tumor size and neutrophil count in patients with RCC, and restoration of miR-124 expression may be effective in the treatment of RCC. He et al (28) reported that miR-125b was significantly upregulated in RCC tissues, which was negatively correlated with vitamin D receptor (VDR) levels. Through mediating VDR, miR-125 is capable of enhancing proliferative and migratory rates of RCC cells, suggesting miR-125 may be a potential therapeutic target of RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Çaykara et al (27) indicated that abnormally downregulated miR-124 was associated with the tumor stage, tumor size and neutrophil count in patients with RCC, and restoration of miR-124 expression may be effective in the treatment of RCC. He et al (28) reported that miR-125b was significantly upregulated in RCC tissues, which was negatively correlated with vitamin D receptor (VDR) levels. Through mediating VDR, miR-125 is capable of enhancing proliferative and migratory rates of RCC cells, suggesting miR-125 may be a potential therapeutic target of RCC.…”
Section: Discussionmentioning
confidence: 99%